On the child image of the educational sciences for teachers - Arató, Ferenc (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This study is an attempt to provide an overview of some essential scientifi c insights that, while not all the discoveries about children from the past rich decades, may still provide a comprehensive picture of the practice. The paper guides the reader through some scientifi c, fact-supported insights, showing a specifi c, introspective example of how it might appear to the practice, as evidenced by science. At the end of the study, it also illustrates how to present scientifi cally proven results as values for practice, values that help formulate principles to follow while supporting practice. It introduces attitudes, practical and methodological principles that may confi dently steer teachers towards a more effective, effi cient and equitable education, as well as researchers in the fi eld of educational sciences.